Effects of combining caffeine and sodium bicarbonate on exercise performance: A review with suggestions for future research - Grgic, J. (Journal of Dietary Supplements, 2020)
This paper aimed to: (a) critically review studies that explored the isolated and combined effects of caffeine and sodium bicarbonate ingestion on exercise performance; (b) discuss some of the possible reasons for the discrepancy in findings; and, (c) provide suggestions for future studies. Out of the eight studies that examined this topic, only one study found that the combined ingestion of both supplements provided additive effects. In other studies, the following findings were observed: (a) only caffeine was ergogenic; (b) isolated and combined ingestion of both supplements was comparably ergogenic; (c) neither isolated nor combined ingestion of caffeine and sodium bicarbonate provided a performance-enhancing effect; and, (d) caffeine and caffeine plus sodium bicarbonate improved performance compared to sodium bicarbonate (but not as compared to placebo). Even though studies used currently recommended protocols of caffeine supplementation and exercise tasks for which the isolated ergogenic effects of caffeine and sodium bicarbonate are already established, the response to sodium bicarbonate supplementation was very variable, which might largely explain the discrepancies in the findings. The protocols of sodium bicarbonate ingestion generally resulted in high incidence and severity of side-effects, which might have had a negative effect on exercise performance. Future studies that optimize protocols of sodium bicarbonate supplementation are needed to fully explore if combining caffeine and sodium bicarbonate indeed provides any additive effects on exercise performance.